A Deeper Dive Into Antibiotic Stewardship Needs: A Multihospital Survey. (11th January 2020) - Vaughn, Valerie M; Petty, Lindsay A; Flanders, Scott A; Malani, Anurag N; Patel, Twisha; Bernstein, Steven J; Hsaiky, Lama M; Thyagarajan, Rama; Osterholzer, Danielle; McLaughlin, Elizabeth; Horowitz, Jennifer K; Gandhi, Tejal N
Abstract: In a 2016 survey of 46 Michigan hospitals, we identified four key needs for antibiotic stewardship: clinically-relevant antibiotic data, monitoring compliance, syndrome-specific interventions, and discharge stewardship. A stewardship initiative now addresses these needs within the Michigan Hospital Medicine Safety Consortium.